Molecular alterations in basal cell carcinoma subtypes - Di Nardo, Lucia; Pellegrini, Cristina; Di Stefani, Alessandro; Ricci, Francesco; Fossati, Barbara; Del Regno, Laura; Carbone, Carmine; Piro, Geny; Corbo, Vincenzo; Delfino, Pietro; De Summa, Simona; Maturo, Maria Giovanna; et al. (Scientific reports, 2021)
A number of genes have been implicated in the pathogenesis of BCC in addition to the Hedgehog pathway, which is known to drive the initiation of this tumour. We performed in-depth analysis of 13 BCC-related genes ( CSMD1, CSMD2, DPH3 promote r, PTCH1, SMO, GLI1, NOTCH1, NOTCH2, TP53, ITIH2, DPP10, STEAP4, TERT promoter) in 57 BCC lesions (26 superficial and 31 nodular) from 55 patients and their corresponding blood samples. PTCH1 and TP53 mutations were found in 71.9% and 45.6% of BCCs, respectively. A high mutation rate was also detected in CSMD1 (63.2%), NOTCH1 (43.8%) and DPP10 (35.1%), and frequent non-coding mutations were identified in TERT (57.9%) and DPH3 promoter (49.1%). CSMD1 mutations significantly co-occurred with TP53 changes ( p = 0.002). A significant association was observed between the superficial type of BCC and PTCH1 ( p = 0.018) and NOTCH1 ( p = 0.020) mutations. In addition, PTCH1 mutations were significantly associated with intermittent sun exposure ( p = 0.046) and the occurrence of single lesions ( p = 0.021), while NOTCH1 mutations were more frequent in BCCs located on the trunk compared to the head/neck and extremities ( p = 0.001). In conclusion, we provide further insights into the molecular alterations underlying the tumorigenic mechanism of superficial and nodular BCCs with a view towards novel rationale-based therapeutic strategies.